2012
DOI: 10.1192/bjp.bp.111.097139
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive development in children with 22q11.2 deletion syndrome

Abstract: The finding of cognitive decline can be only partly explained as the result of 'growing into deficit'; about a third of 29 children showed an absolute loss of cognitive faculties. The results underline the importance of early psychiatric screening in this population and indicate that further study of the genes at the 22q11.2 locus may be relevant to understanding the genetic basis of early cognitive deterioration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
82
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 36 publications
7
82
2
1
Order By: Relevance
“…Thus, available data suggests that (1) cognitive decline during childhood may not be present in all genetic disorders associated with mental retardation, and (2) it is uncertain to what extent an absolute decrease in IQ, such as reported here, is common in genetic disorders other than 22q11DS. The results of the current study replicate, in a different age group, our previous findings in younger children (Duijff et al, 2012). The results also support the suggestion that children whose IQ appears relatively stable up to their early teens may still go on to decline in adolescence or adulthood (Evers, De Die-Smulders, Smeets, Clerkx, & Curfs, 2009).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, available data suggests that (1) cognitive decline during childhood may not be present in all genetic disorders associated with mental retardation, and (2) it is uncertain to what extent an absolute decrease in IQ, such as reported here, is common in genetic disorders other than 22q11DS. The results of the current study replicate, in a different age group, our previous findings in younger children (Duijff et al, 2012). The results also support the suggestion that children whose IQ appears relatively stable up to their early teens may still go on to decline in adolescence or adulthood (Evers, De Die-Smulders, Smeets, Clerkx, & Curfs, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…Sixteen of the children reported in this study have also been described in an earlier article on the development of children between the age of 5 and 9 (Duijff et al, 2012). Including this data in the current study in a posthoc analysis allowed for the analysis of the development of cognitive abilities of children with 22q11DS from the age of 7.5 (T0).…”
Section: Methodsmentioning
confidence: 87%
“…Frequently associated medical conditions include conotruncal cardiac anomalies, palatal anomalies (including velopharyngeal insufficiency), hypoparathyroidism/hypocalcemia, and subtle dysmorphic facial features (1). The neurocognitive profile is also highly variable, both between individuals and during the course of development (2). From infancy onward, motor delays (often with hypotonia) and speech or language deficits are commonly observed (3).…”
mentioning
confidence: 99%
“…developmental lag - is expected in children in the lower IQ range, 3032 a recent prospective longitudinal study found that about one-third of children with 22q11DS under age 10 not only display cognitive deficit relative to age norms, but also an absolute decline in cognitive abilities. 33 Collectively, these initial studies suggest that in patients with 22q11DS, as in the general population, both early cognitive deficits as well as early cognitive decline could portend schizophrenia.…”
mentioning
confidence: 99%